The practices of antibiotics application in neurosurgical patients in Ukraine: a cohort study - Berezhna, Antonina; Makarova, Victoria; Chumachenko, Tetyana (Journal of Education, Health and Sport, 2021)
Introduction. The outcomes of potential complications of surgical interventions in neurosurgical patients can cause a death. Efficient antibiotic prophylaxis decreases the risks of infection and improves the quality of health care. Purpose. To estimate the appropriateness of prescribing antibiotics in a neurosurgical ward from the perspective of evidence-based medicine. Material and method. A retrospective cohort study has been carried out in a neurosurgical ward of multidisciplinary healthcare setting of Ukraine. Data from 131 in-patient medical cards (MC) of neurosurgical patients has been analyzed. Descriptive statistics methods have been used for data analysis. The relative risk (RR) with the 95% confidence interval (95% CI) has been calculated. Results. We found that among the patients, females prevailed (n = 81 / 61.8%). The patients’ mean age was 49.83 ± 13.90 years. The frequency of antibiotics prescriptions was higher significant in patients, who received surgical procedures in comparison with patients, who did not receive surgical procedures (RR = 1.827; 95% CI: 1,137 – 2.935). Antibiotics were prescribed mostly during the postoperative period. The use of interchangeable antibiotics of the same group has been occurred. The use of antibiotics for prevention in the most cases was of unreasonably long duration. Conclusion. The practice of the use of antibiotics in neurosurgical ward does not correspond to scientifically founded recommendations. It is needed to clearly define the indications for prescribing antibiotics. Duration of antibiotic use should depend on specialization of wards in multidisciplinary healthcare setting. It is expedient to conduct an audit on the use of antibiotics at healthcare settings on a regular basis with involving a specialist in infection control, a clinical pharmacist, and a clinical microbiologist.